FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR - Muhammad Rizky Al-Khairi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
There is differences time in the company’s financial report to the capital market can be caused by some factors like profitability, company age, auditor substitution, and reputation of KAP. Issues in this research was how profitability, company age, auditor substitution, and reputation of KAP can be effect to audit report lag in partial and simultan. This research analyze with double regression. Result of this research indicate that profitability, company age and reputation of KAP is not influential audit report lag. While auditor substitution is influential audit report lag in partial. The combined of profitability, company age, auditor substitution, and reputation of kap are influential audit report lag on simultan.